PERBANDINGAN PENELITIAN FINANCIAL DISTRESS PADA BANK UMUM KONVENSIONAL DI INDONESIA - Akyuwen, Roberto; Rahmatika, Dien Noviany; Subagyo, Ahmad (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
ABSTRACT Financial distress is a common phenomenon occurred in the business organizations, including banking industry. The financial distress banks will experience significant decline in their financial performance which require an immediate improvement to mitigate the worsen condition and bankruptcy. This research is aimed to compare previous studies on financial distress in the conventional commercial banks in Indonesia undertaken by various researchers. In overall, 30 relevant researches from the period of 2015 to 2021 will be compared and analyzed. The comparison will cover the use of different tools of analysis, dependent and independent variables, and relationship patterns among those variables. The result shows that logistic regression is the most frequent tools of analysis used by researchers in identifying the financial distress condition in the conventional commercial banks in Indonesia. Meanwhile, dummy variable is the most intensive dependent variable used in various studies. Most of researchers have used NPL, CAR, and ROA as independent variables in their researches. Furthermore, there were inconsistent influence pattern of various factors on financial distress. Keywords: comparison; conventional commercial banks; financial distress. ABSTRAK Kesulitan keuangan (financial distress) merupakan fenomena yang umum terjadi dalam organisasi bisnis, termasuk industri perbankan. Bank yang sedang dalam kesulitan keuangan biasanya mengalami penurunan signifikan dalam kinerja keuangan dan memerlukan perbaikan segera untuk meminimalkan risiko terjadinya kondisi yang lebih buruk dan kebangkrutan. Penelitian ini bertujuan untuk membandingkan penelitian-penelitian sebelumnya mengenai kesulitan keuangan pada bank umum konvensional di Indonesia yang dilakukan oleh berbagai peneliti. Secara keseluruhan, sebanyak 30 penelitian yang relevan selama periode 2015-2021 dibandingkan dan dianalisis. Perbandingan ini meliputi penggunaan berbagai alat analisis, variabel dependen dan independen, dan pola hubungan antar variabel tersebut. Hasil penelitian menunjukkan bahwa regresi logistik merupakan alat analisis yang paling sering digunakan dalam mengidentifikasi kondisi kesulitan keuangan pada bank-bank umum konvensional di Indonesia. Sementara itu, dummy variable merupakan variabel dependen yang paling banyak dipakai dalam berbagai studi. Mayoritas peneliti telah menggunakan NPL, CAR, dan ROA sebagai variabel independen dalam penelitian mereka. Selanjutnya, terdapat pola yang tidak konsisten dalam pengaruh berbagai faktor terhadap kesulitan keuangan. Kata kunci: perbandingan; bank umum konvensional; financial distress.